Interaction Structure and Pragmatic Features in the 2008 National Quasi-Judicial Public Hearing on the Federal Capital Territory Administration in Nigeria (2012)
Studies on quasi-judicial public hearings have focused on rhetorical, sociolinguistic and critical discourse aspects of the hearings, but have not given attention to the discourse structure and participant goals during the hearings. Thus, this study examined language use and interaction in the 2008 quasi-judicial public hearing, conducted by a hearing panel constituted by the Senate on the Federal Capital Territory (FCT) administration in Nigeria. This was done with a view to revealing the interactional formats and pragmatic roles of language in the hearing and comparing the formats with those of the Truth and Reconciliation Commission (TRC) hearing study in South Africa, the only quasi-judicial public hearing yet analysed in Africa. Generic Structure Potential and pragmatic theories provided the theoretical framework for the study because they deal with interactional structures and functions of language in context. Forty purposively sampled video recordings of the hearing were obtained from the African Independent Television stations in Abuja and Lagos. These were complemented with structured interviews with the complainants, newspaper reports, written submissions and the final report of the panel. The data were subjected to content analysis. Ten discourse macrostructural elements characterised the generic structure of the public hearing. These were catalogued as: AO ^ A^ IP ^ [P(Pr)] ^ {I ^ IC}n ^ (PD) ^ (Pr) ^Ad ^ (F) Affirmation Order, Affirmation, Invitation of Perspectives, Presentation, Interrogation, Interrogation Compliance and Admission were obligatory while Prayer Demand, Prayer and Finis were optional. Interrogation and Interrogation Compliance were iterative at equal degrees. Prayer was either a part of Presentation or a pre-Admission occurrence. These interaction structure elements were variously characterised by discourse and pragmatic features. Locutions in the hearing featured jargon, plain words, fixed and free collocations; affixation, compounding, abbronymy and clipping; antonyms and synonyms; and declaratives, interrogatives and imperatives. Contextual beliefs were based on shared knowledge of public hearing procedures, shared knowledge of landed property law, shared knowledge of government involvement and shared knowledge of Abuja metropolis. Thirteen pragmatic acts characterised the language: ordering, swearing, appreciating, informing, complaining, defending, advising, commenting, denying, questioning, promising, requesting and admitting. Five macrostructures in the FCT hearing were similar to those of the TRC hearing, namely, Affirmation Order/introduction, Invitation of Perspectives/elicitation, Presentation/narrative, Interrogation/questions and Finis/concluding remarks. Affirmation, Interrogation Compliance, Prayer Demand, Prayer and Admission were not identified in the latter. The TRC study, using a narrative approach, did not give any attention to generic structure and pragmatic functions, which constituted major findings on the FCT hearing. Generic Structural elements and pragmatic properties provide useful insights into the discourse and procedure of the 2008 FCT hearing. Unlike the study on the FCT which captures the interactional specifics of the hearing, the structures identified in the TRC study were broad and did not cover details of the interaction. Thus, in-depth comparative linguistic studies of quasi-judicial public hearings in Nigeria and other African countries are required to have a clearer understanding of the structure and pragmatic constraints in the hearings.